Contextual factors associated with the morale of academic and support staff in universities. (3rd April 2023) - Sell, Andrea J.
ABSTRACT: This paper provides a review of the contextual factors that are associated with levels of morale and job satisfaction in academic institutions. It argues that universities can purposefully create workplace environments that support employee well-being by measuring, attending to, and addressing levels of collegiality; designing policies that introduce greater work–life balance; developing robust mentoring programmes; ensuring that systems are in place to allow members of academic and support staff to recognise each other's work; and maintaining transparency in decision-making and resource allocation. Recommended assessments and suggested intervention resources are also noted.